Family Counselling Enhances Environmental Control of Allergic Patients - Santi Dwi Lestari; Lailatun Nikmah; Ninuk Dian Kurniawati (Universitas Airlangga, 2019)
Introduction: Allergies can cause complications such as inadequate nutrition, impaired sleep quality, and inhibition of child growth and development. There were about 15% children who suffered from dust allergies in 2017 in Indonesia. Parents lacking of knowledge about environmental control can increase the prevalence of allergic relapse in children. Counselling is a method of health education that aims to improve knowledge, and practice. The purpose of this study was to investigate whether counselling has any influence on allergic related knowledge and environmental control measures skills.Methods: The design of study was a pre-experiment design. There were 14 respondents in this study who were recruited at a university hospital based on inclusion criteria with consecutive sampling. The independent variable was counselling, the dependent variable were knowledge and environmental control measures. Data were collected using both a questionnaire was developed from the AAAAI and a check list was used to determine parents' skills on environmental controls. Data were analysed using Wilcoxon Sign Rank Test with significance level of α<0,05.Results: There was an influence of counselling on knowledge and environmental control measures (knowledge level, p= 0,001; practice level p= 0,001).Conclusion: It is concluded that counselling is significantly increased knowledge and environmental control measures level.